Protection for Migrant Workers under Evolving Occupational Health and Safety Regimes in China - Li, Mankui (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2017)
Migrant workers in China are a distinctive group due to the existence of the hukou system under which they continue to face restrictions on housing, education, and health care in urban areas. The equal employment legislation does not solve the discrimination problems. Compared with their urban counterparts, migrant workers are more vulnerable, in terms of both precarity of employment and the occupational hazards that they are exposed to, and badly need OHS protection. Any weakness of OHS regime will have a disproportionately adverse effect on migrant workers.China’s OHS regime has been through constant evolution. The old prevention structure, which separated occupational health from occupational safety, was proved to be less effective in protecting migrant workers. In recognition of its deficiencies, China’s top legislature made adjustments to the OHS legal framework by enacting and updating a series of laws. The new prevention structure, unifying the occupational health administration and the occupational safety administration, represents a step forward in terms of OHS protection for migrant workers.According to worker citizenship theory, China’s OHS regime can be categorized as a direct state regulation model. It carries with it both the strengths and weaknesses of direct state regulation models. On the participation rights dimension, the lack of consultative joint OHS committees and the lack of effective collective bargaining shut migrant workers out from the decision-making process on OHS matters. On the social rights dimension, the gendered and aged-based approach becomes a hindrance for female migrant workers and young migrant workers. Furthermore, levels of enforcement vary considerably across different periods and areas, subject to the ever-changing priorities on the government’s agenda. Migrant workers are still facing tremendous obstacles and challenges in obtaining access to adequate protection under the current OHS regime in China. Future reform measures should focus on delivering OHS protection for migrant workers in the informal sector, strengthening participation, and centralizing OHS administration, especially enforcement.